Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jcmm.16726
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of five column‐based isolation kits and their ability to extract miRNA from human milk

Abstract: MicroRNA can be found in various body fluids, including breast milk. MicroRNA may be transferred from mother to infant via breast milk and potentially regulate the development of the infant's immune system on a post‐transcriptional level. This study aimed to determine the microRNA extraction efficiency of five RNA extraction kits from human skim milk samples. Their efficiency was determined by comparing microRNA concentrations, total RNA yield and purity. Furthermore, hsa‐miR‐148a‐3p expression and the recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…13 Besides, in milk exosomes, researchers have also detected the presence of miRNAs in milk components such as milk fat and whey of bovine milk or human milk, respectively. 14,15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Besides, in milk exosomes, researchers have also detected the presence of miRNAs in milk components such as milk fat and whey of bovine milk or human milk, respectively. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…13 Besides, in milk exosomes, researchers have also detected the presence of miRNAs in milk components such as milk fat and whey of bovine milk or human milk, respectively. 14,15 However, it is so far unclear how mature miRNAs are selectively wrapped/loaded into exosomal vesicles, which may depend on the surface molecules of the exosome membrane, the specific proteins required for transport, and the specific binding motifs of the miRNAs themselves. For example, Shurtleff et al (2016) suggested that the RNA-binding protein Y-box protein I may play an essential role in the secretion of miRNAs into exosomes by HEK293T cells.…”
Section: Introductionmentioning
confidence: 99%
“…In RNA, absorbance at A260 primarily measures nucleic acids, indicating the RNA concentration; absorbance at A280 detects proteins; and absorbance at A230 identifies organic compounds. Also, RNA has a higher 260/280 ratio due to the ratio of Uracil (4.00) compared to that of Thymine (1.47) [17]. This is validated through spectrophotometry using the 260/280 ratio, with an optimal value above 2.0 for RNA [18], and the 260/230 ratio, with an optimal value of 2.2 [19].…”
Section: Rna Purity and Concentrationmentioning
confidence: 85%
“…This is validated through spectrophotometry using the 260/280 ratio, with an optimal value above 2.0 for RNA [18], and the 260/230 ratio, with an optimal value of 2.2 [19]. Values above 2.0 for the A260/280 ratio indicate the absence of protein contamination, and values above 2.0-2.2 for the A260/230 ratio indicates the absence of solvent contamination and denote the isolation of high-quality, non-contaminated, or pure RNA [17,20].…”
Section: Rna Purity and Concentrationmentioning
confidence: 99%
“…On the other hand, recent reports on methodology of miRNA extraction demonstrated higher efficiency of column-based isolation kits compared to Trizol [257,258]. However, different kits apply nonidentical protocols, resulting in variable RNA yield and purity [259,260].…”
Section: Discussionmentioning
confidence: 99%